PENERAPAN MODEL PROBLE BASED LEARNING (PBL) TERHADAP KEMAMPUAN KOGNITIF MATEMATIK PESERTA DIDIK KELAS V A DI SDN CIGABUS - Desty Wahyuhandini; Indhira Asih V.Y; Trian Pamungkas Alamsyah (STKIP Subang, 2023)
This study aims to determine whether there is an effect of applying the problem-based learning model to the mathematical cognitive abilities of students in class 5 A at SDN Cigabus. The method used in this study was quasi-experimental, with the design used in the form of a Nonequivalent Control Group Design. The samples used in this study were students in class VA as experimental class 1, totaling 25 students using the problem-based learning model and class VB as experimental class 2, totaling 25 students using the direct learning model. The analysis technique in this study is the T-test. Based on the calculation results, it was obtained a comparison of the test criteria between tcount ≥ ttable or 2.01 ≥ 1.42. From these results it was stated that there were differences in the mathematical cognitive abilities of students between experimental class 1 and experimental class 2, so that indicators of cognitive mathematical abilities of students in the experimental class 1 is higher when compared to experimental class 2 and indicators of cognitive mathematical abilities of students in experimental class 1 are categorized both in volume and cube material.